EDUCATION A GENDER ACTIVITY - A. Ali; A. Saghir; M. Z. Y. Hassan (Journal of Animal and Plant Sciences, 2006)
Gender roles are significant in several sectors of life. Teaching is a revolutionary profession to get change of a nation. Women are especially dominant in this field. As it is considered a safe and respectable profession for women. They participate in formal, non-formal, technical, professional, scientific and religious education as well. The present study was designed to determine socioeconomic status of women teachers and their participation towards household and community development in Faisalabad Distt. In order to make the whole representation of the universe stratified sampling from madrassa, primary school, high school, and college one each from urban and rural area was selected randomly. From research-selected institutions 15 respondents were randomly selected from madras, primary school, high school and college from both rural and urban areas, however 15 respondents were selected from university, which was located only in only to urban area. Thus making a total of 135 women teacher respondents. After pre-testing of interview schedule, data were collected. Tabulated and analyzed through SPSS (Statistical Package for Social Sciences).The results showed remarkable participation of women in economic activities through educational profession but on the cost of their house and children. Govt. should design policies on sustained basis considering their need and role in country’s’ economy.
Keywords: Gender; Education; Occupational; Social Sciences.